Optimizing Bonding Parameters for Glued Laminated Timber from Fast-Growing Laran Species Using Polyurethane Adhesive - Muhammad Amirul Akmal Rosli; Norshariza Mohamad Bhkari; Zakiah Ahmad; Ameera Amani Amrudin; Muhammad Bazli Faliq Mohd Puaad; Norman Wong Shew Yam (International Journal of Integrated Engineering, 2025)
This study investigates the optimization of bonding parameters for glued laminated timber (glulam) made from fast-growing Laran species using Polyurethane (PUR) adhesive, focusing on the adhesive spread rate and press pressure. The research aims to determine the shear strength, delamination properties, and wood failure percentage of Laran glulam, contributing to the sustainable use of fast-growing timber species in engineered wood products. The results showed a complex relationship between adhesive spread, press pressure, delamination, shear strength, and wood failure percentage. Higher press pressures generally reduced delamination but also decreased shear strength and increased wood failure. The optimal bonding parameters, determined through response surface methodology (RSM), were a adhesive spread of 400 g/m2 and a press pressure of 0.74 MPa, yielding a predicted shear strength of 7.68 N/mm2 and a wood failure percentage of 83.74%, although the predicted total delamination slightly exceeded the acceptable limit. The study successfully identified the optimal bonding parameters for Laran glulam using PUR adhesive, highlighting the trade-offs between delamination resistance and shear strength and underscoring the potential of Laran in glulam production.